The influence of non-selective and selective-COX-2 NSAIDs post-minor surgery for the turning of the bleeding time. - Ishandono Dachlan, Ishandono Dachlan (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2001)
Background: NSAIDs remain among the most widely prescribed drugs worldwide, including for surgical cases. Their action are primarily by inhibiting cyclo-oxigenase (COX), the key enzyme catalyzing the biosynthesis of prostaglandins (PGs). There are two similar but distinct isoforms of the enzyme - COX-1 and COX-2. One of the effects of COX-1 inhibition (nonselective NSAIDs) is decreasing thromboxanes, which is one of the important factors in thrombocytes aggregation and blood clotting. The optimal thrombocyte aggregation is required in many surgical cases, especially in microsurgery.Objective: The aim of this study is to compare the influence of non-selective and selective-COX-2 NSAIDs in the turning of the bleeding time.Methods: A prospective study of five days using NSAIDs has been done. The subjects were randomly distributed into two groups, non-selective group and selective COX-2 inhibitor group. The bleeding time was measured prior and after five days using of NSAIDs. The result was analyzed with t-test. Results: The mean of the prior bleeding time was 2.85 minutes (non-selective group) and 2.90 minutes (selective-COX-2 Inhibitor group). After five days using of NSAIDs, the bleeding time was increased from 2.85 to 3.15 minutes (non-selective group) and 2.90 to 2.95 minutes (selective COX-2 Inhibitor group). The mean of the bleeding time difference were 0.3 minutes (non-selective group) and 0.05 minutes (selective COX-2 Inhibitor group). T-test analysis showed that bleeding time was increased significantly from 2,85 minutes up to 3.15 minutes (p=0.005) after five days using non-selective NSAIDs, while there was no significant increase of bleeding time, from 2.90 minutes up to 2.95 minutes (p=0.591) after five days using of selective COX-2 inhibitor NSAIDs.Conclusion: Selective COX-2 inhibitor NSAIDs did not increase the bleeding time, while non-selective NSAIDs increased bleeding time after five days usage.Keyword: NSAIDs - selective - COX2 inhibitor - bleeding time - thromboxanes